Indigenas Amarakaeri - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó a dos indigenas Amarakaeri vestidos tradicionalmente llamado cushma sosteniendo sus armas de caza unas flechas.
ENGLISH: Two Amarakaeri indigenous people dressed traditionally called cushma were observed holding their hunting weapons and arrows.

SPANISH: Se observó a dos indigenas Amarakaeri vestidos tradicionalmente llamado cushma sosteniendo sus armas de caza unas flechas.
ENGLISH: Two Amarakaeri indigenous people dressed traditionally called cushma were observed holding their hunting weapons and arrows.
Amarakaeri indigenous people
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Hunting Weapons|~|Production|~|Food|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Armas de Caza|~|Poducción|~|Alimentación|~|/ Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Hunting Weapons|~|Production|~|Food